PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN PARTISIPASI DAN PEMAHAMAN SISWA SEKOLAH DASAR - Lasmiati; Jayanti; Priska, Ice; Rahmadilla, Riska; Pakpahan, Dina; Ari Barkah, M.; Alifah, Siti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of the Problem Based Learning (PBL) model in elementary schools, analyze the improvement of student participation, and evaluate students’ conceptual understanding after the implementation of the model. This study employed classroom action research consisting of two cycles involving 27 fifth-grade students at SD Negeri 226 Palembang. The research instruments included student participation observation sheets, group worksheet (LKPD) assessments, and individual evaluation tests. Each cycle consisted of planning, implementation, observation, and reflection stages. The findings showed a significant improvement in student participation. The percentage of students asking questions increased from 44% in Cycle I to 74% in Cycle II, answering questions from 63% to 81%, participating in discussions from 67% to 89%, and presenting from 78% to 93%. Students’ conceptual understanding also improved, indicated by the increase in the average LKPD score from 73.3 to 84.7 and the average individual evaluation score from 76.3 to 88.9. These findings indicate that the PBL model effectively improves student participation and conceptual understanding in elementary school learning. Kata Kunci: Problem Based Learning; student participation, understanding concepts, elementary school, Active Learning